Hepatic Unsaturated Fatty Acids Are Linked to Lower Degree of Fibrosis in Non-alcoholic Fatty Liver Disease - Fridén, Michael; Rosqvist, Fredrik; Ahlström, Håkan; Niessen, Heiko G.; Schultheis, Christian; Hockings, Paul; Hulthe, Johannes; Gummesson, Anders; Wanders, Alkwin; Rorsman, Fredrik; Risérus, Ulf; Vessby, Johan (Frontiers in Medicine, 2022)
Background: The hepatic lipidome of patients with early stages of non-alcoholic fatty liver disease (NAFLD) has been fairly well explored. However, studies on more progressive forms of NAFLD, i.e. liver fibrosis, are limited. Material and methods: Liver fatty acids were determined in cholesteryl esters (CE), phospholipids (PL) and triacylglycerols (TAG) by gas chromatography. Cross-sectional associations between fatty acids and biopsy-proven NAFLD fibrosis (n=60) were assessed using multivariable logistic regression models. Stages of fibrosis were dichotomized into none-mild (F0-1) or significant fibrosis (F2-4). Models were adjusted for body-mass index (BMI), age and patatin-like phospholipase domain-containing protein 3 (PNPLA3 rs738409) (I148M) genotype. A secondary analysis examined whether associations from the primary analysis could be confirmed in the corresponding plasma lipid fractions. Results: PL behenic acid (22:0) was directly associated (OR (95% CI): 1.86 (1.00, 3.45)) whereas PL docosahexaenoic acid (22:6n-3) (OR (95% CI): 0.45 (0.23, 0.89)), TAG oleic acid (18:1n-9) (OR (95% CI): 0.52 (0.28, 0.95)) and 18:1n-9 and vaccenic acid (18:1n-7) (18:1) (OR (95% CI): 0.52 (0.28, 0.96)) were inversely associated with liver fibrosis. In plasma, TAG 18:1n-9 (OR (95% CI): 0.55 (0.31, 0.99)), TAG 18:1 (OR (95% CI): 0.54 (0.30, 0.97)) and PL 22:0 (OR (95% CI): 0.46 (0.25, 0.86)) were inversely associated with liver fibrosis. Conclusion: Higher TAG 18:1n-9 levels were linked to lower fibrosis in both liver and plasma, possibly reflecting an altered fatty acid metabolism. Whether PL 22:6n-3 has a protective role, together with a potentially adverse effect of hepatic 22:0, on liver fibrosis warrants large-scale studies.